Daya Saing Usahatani Tebu terhadap Komoditas Eksisting di Wilayah Kerja Pabrik Gula Wonolangan Kabupaten Probolinggo Tahun 2018 - Trikuntari Dian Pratiwi; Evan Pratama Wibowo; Heru Wibowo (Caraka Tani: Journal of Sustainable Agriculture, 2018)
This study aims to describe in general the performance of Wonolangan Sugar Factory and to analyze the comparison of sugarcane farming with a non-sugarcane commodity in the working area of Wonolangan Sugar Factory. Wonolangan Sugar Factory is located in Probolinggo Regency, almost 90% of sugarcane raw material is obtained from Lumajang Regency. Commodities that become competitors and the main choice of farmers to be cultivated are rice, maize, and onion. The data used in this study are primary and secondary data. The sampling method used is purposive with in-depth interview technique. Portrait performance of Wonolangan Sugar Factory in the last 5 years is very fluctuating caused by various factors such as climate impacts that are less supportive, the motivation of farmers to grow sugarcane, government policy in the sugar industry. To maintain the smoothness of the mill in the implementation of milling, Wonolangan Sugar Factory has several strategies both on the farm (garden) and off-farm (sugarcane processing at the factory). Based on the comparison of Sugar Business Result (SHU) of sugarcane and non-sugarcane planting pattern, it appears that the analysis shows that sugarcane farming with one Ratoon Cane (RC) category in paddy field can only compete with the pattern of non-cane maize farming throughout the year in South Sugar Factory Wonolangan.